The effect of implicit theories of pain on pain and disability in people with chronic low back pain. (April 2019) - Summers, Simon J.; Higgins, Nancy C.; Te, Maxine; Byrne, Ailish; Chipchase, Lucy S.
Abstract: Background: Implicit theories of pain represent a socio-cognitive mechanism linked to important coping, emotional, and expressive reactions to chronic pain. Evidence suggests that chronic low back pain (CLBP) patients who hold an incremental theory of pain (i.e., view pain as a malleable) use more active coping strategies, display less pain behavior, and report lower levels of depression than those with an entity theory of pain (i.e., view pain as a fixed). However, a link between implicit theories of pain and symptoms of pain and disability in people with CLBP has not been established. Objectives: This study investigated the relationship between implicit theories of pain and the level of pain and disability reported by people with CLBP. Design: Cross-sectional observational study. Methods: One hundred and two participants with CLBP completed an online survey distributed through social media channels. The online survey assessed pain intensity and pain-related disability (Chronic Pain Grade Scale), implicit theories of pain (Implicit Theory of Pain Scale), and perceived control over pain (Survey of Pain Attitudes control scale). Results: Participants with an incremental theory of pain reported significantly less pain and disability compared to those with an entity theory of pain (p < 0.001). Conclusions: These findings suggest that implicit theories of pain may guide self-reported symptoms of pain and disability in a CLBP population. Prospective studies are required to confirm the relevance of these findings for risk of future low back pain, and to confirm whether this relationship changes with and without treatment. Highlights: Implicit theories of pain were explored in people with chronic low back pain (CLBP). Individuals were sub-grouped into two implicit theories: entity and incremental. Relationship between implicit theories, pain and disability was assessed. Compared to entity theorists, incremental theorists had less pain and disability. Implicit theories of pain may be a relevant target for future treatment in CLBP.